Impact of lockdown on patients with congestive heart failure during the coronavirus disease 2019 pandemic. (30th September 2020) - Chagué, Frédéric; Boulin, Mathieu; Eicher, Jean‐Christophe; Bichat, Florence; Saint Jalmes, Maïlis; Cransac‐Miet, Amélie; Soudry‐Faure, Agnès; Danchin, Nicolas; Cottin, Yves; Zeller, Marianne
Abstract: Aims: Cardiovascular co‐morbidities like congestive heart failure (CHF) alter the course of coronavirus disease 2019. Factors associated with the outbreak and lockdown can exacerbate CHF. Methods and results: We analysed the answers of 124 randomly selected CHF outpatients (mean age 71.0 ± 14.0 years, 60.5% male) interviewed by phone during the sixth and seventh weeks of the lockdown. Most patients were treated for New York Heart Association class II (38.7%) and reduced ejection fraction HF (70.2%). Psychological distress (Kessler 6 score ≥ 5) was common (18.5%), and 21.8% felt worse than before the lockdown. Few patients ( n = 10) adjusted their intake of HF medications, always on medical prescription. Decreased physical activity was common (41.9%) and more frequent in women ( P = 0.025) and urban dwellers ( P = 0.009). Almost half of respondents (46.0%) declared increased screen time, but only few declared more alcohol intake (4.0%). Weight gain was common (27.4%), and 44.4% of current smokers increased tobacco consumption. Adherence to recommended salt or fluid intake restrictions was reduced in 14.5%. Increase in HF symptoms was commonly reported (21.8%) and tended to be higher in women than in men ( P = 0.074). Of the 23 patients who had a phone teleconsultation during the pandemic, 16 had initially planned an in‐person consultation that they switched for teleconsultation. Conclusions: During the lockdown, psychological distress and decreased well‐being were common in CHF outpatients, and there was an increase in unhealthy lifestyle behaviours. These changes may negatively impact short‐term and long‐term prognoses. Medication adherence was maintained, and limitations in access to care were partly counterbalanced by use of telehealth.